2013
DOI: 10.3996/082012-jfwm-071
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Monitoring of an Endangered Desert Fish and Factors Influencing Population Dynamics

Abstract: The lower perennial corridor of the Little Colorado River in Grand Canyon, Arizona, is numerically dominated by endemic desert fishes and therefore significant for conservation of these species. From 2000 to 2012, the U.S. Fish and Wildlife Service conducted monitoring of native fishes in the Little Colorado River near its confluence with the Colorado River. The primary focus of these efforts was to estimate the spring and fall abundance of native fishes, especially the federally endangered humpback chub Gila … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 26 publications
0
59
1
Order By: Relevance
“…It is unknown why Little Colorado River condition increased over this interval, but Van Haverbeke et al (2013) found increasing trends in abundance since 2000 of Humpback Chub, Flannelmouth Sucker Catostomus latipinnis, and Bluehead Sucker Catostomus discobolus in the Little Colorado River, with some of the highest abundance estimates occurring in 2009-2011. These increases in condition and abundance may be the result of improved growing conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unknown why Little Colorado River condition increased over this interval, but Van Haverbeke et al (2013) found increasing trends in abundance since 2000 of Humpback Chub, Flannelmouth Sucker Catostomus latipinnis, and Bluehead Sucker Catostomus discobolus in the Little Colorado River, with some of the highest abundance estimates occurring in 2009-2011. These increases in condition and abundance may be the result of improved growing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Cross et al (2011) documented that prey consumption rates by fishes in the Colorado River nearly equaled or exceeded invertebrate production, which may cause food limitation that could lead to lower condition. We were only able to estimate length-weight relationships for 1 y (2011) during the time period Van Haverbeke et al (2013) noted increasing abundance for Humpback Chub; but in this one year Humpback Chub showed the most robust size for a given length of all the years we examined (Figures 2 and 3). Despite the increasing temporal trend in Humpback Chub length-weight relationships in the Little Colorado River, condition in this important tributary is still below that of juvenile Humpback Chub occupying the mainstem Colorado River.…”
Section: Discussionmentioning
confidence: 99%
“…A1.3). The 2-year cycle appears to break down after 2009, but the highly variable annual chub production in the Little Colorado River reported by Van Haverbeke et al (2013) between 2001-14, does not bode well for managers who hope to detect recruitment responses quickly after short experimental treatments focused on native chub are started. Net recruitment of native fish to older ages does appear to have responded positively over the 2003-06 treatment period of experimental non-native fish removal from the Colorado River ecosystem mainstem near the Little Colorado River confluence (Coggins et al 2011).…”
Section: Sandbarsmentioning
confidence: 99%
“…This sampling program provides data for estimating trends in abundance and recruitment within the LCR using mark-recapture methodologies. Specifically, a Chapman modified Petersen closed population estimator (see Seber, 1982) has been used to estimate seasonal abundance (Van Haverbeke et al, 2013). In more recent years, an age structured open population model was developed to evaluate age-specific annual mortality probabilities as well as abundance and recruitment trends .…”
Section: Introductionmentioning
confidence: 99%